Factors related to life satisfaction among urban African American adults receiving care at a publicly-funded sexual health clinic - Dunne, Eugene M. (Psychol Health Med, 2017)
Life satisfaction is linked to premature morbidity and mortality and it may be compromised for individuals living in economically-disadvantaged, urban neighborhoods. The present study explores how behavioral and social-environmental health factors are associated with life satisfaction among a sample of African American young adults. Participants (N = 307, M(age) = 26.6 years, 53% male) were recruited from a publicly-funded clinic for a randomized controlled trial (RCT). Data from the baseline assessment of the RCT, which included measures of sleep, depression, anxiety, social support, alcohol and drug use problems, city stress, and life satisfaction, were used for the current study. Correlation analyses assessed bivariate associations between life satisfaction and the demographic and health-related factors. Linear regression using backward elimination determined the best fitting model of factors associated with life satisfaction. Backward elimination resulted in the following variables remaining as significantly associated with life satisfaction: age (b = −2.40, p = .017), anxiety (b = −5.32, p < .001), and social support (b = 2.89, p = .004). Feeling rested upon waking also remained in the best fitting model, although this association did not achieve statistical significance (p = .099). The results suggest that African American adults who are younger, less anxious, and report adequate social support are more likely to report satisfaction with life. These findings add to the literature aimed at examining health and social factors impacting the well-being of African Americans living in low-income, urban communities.